Planning dam operation and irrigation development on the Blue Nile in Sudan - Basheer, Mohammed; Siddig, Khalid; Ringler, Claudia (2022)
Mohammed Basheer, Khalid Siddig, and Claudia Ringler 2nd Pakistan Water Week October 24-28, 2022